2010
DOI: 10.1016/j.jallcom.2009.09.042
|View full text |Cite
|
Sign up to set email alerts
|

The z value dependence of photoluminescence in Eu2+-doped β-SiAlON (Si6−zAlzOzN8−z) with 1≤z≤4

Abstract: Eu 2+ -doped -SiAlON (Si 6-z Al z O z N 8-z ) phosphors with 1  z  4 were synthesized by gas pressure sintering. The emission spectra exhibit two broad bands with maxima at about 415 nm (violet) and 540 nm (green) under ultraviolet excitation. The green emission is dominant at z  2, while the violet emission becomes dominant at z > 2. The combination of two emission bands in a compound could lead to a white emission in Eu 2+ -doped -SiAlON with 2 < z  3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 22 publications
3
35
0
Order By: Relevance
“…Multi-color emission has been also reported for several phosphors doped with only Eu 2+ [8,9], where several crystallographic sites in their host structure were simultaneously substituted by Eu 2+ . Kikkawa et al reported three emission peaks at 400, 475 and 520 nm for Eu 2+ -doped AlON with an impurity phase of magnetoplumbite (MP)-type EuAl 12 O 19 [10].…”
Section: Introductionmentioning
confidence: 79%
“…Multi-color emission has been also reported for several phosphors doped with only Eu 2+ [8,9], where several crystallographic sites in their host structure were simultaneously substituted by Eu 2+ . Kikkawa et al reported three emission peaks at 400, 475 and 520 nm for Eu 2+ -doped AlON with an impurity phase of magnetoplumbite (MP)-type EuAl 12 O 19 [10].…”
Section: Introductionmentioning
confidence: 79%
“…In addtion, a broad emission band peaking at 527 nm is also present. Our previous studies revealed that the Eu 2+ -doped ␤-sialon with z = 4 exhibits a violet emission band peaking at 409 nm [28]. Thus, the decomposed emission band peaking at 408 nm is believed to result from the ␤-sialon present also as a major phase in the product obtained at 1700 • C (Fig.…”
Section: Emission Mechanismmentioning
confidence: 90%
“…The optical properties of the oxynitrides in the UV-vis range have been explained by the coexistence of nitride and oxide anions together because of the more covalent nature in nitride ion [13]. Much research on phosphor materials for LED applications has been conducted on silicon oxynitride and alumino-silicon oxynitrides as host materials [14][15][16]. However, study on (oxy)nitrides of especially aluminum is limited to systems such as AlN:Eu, spinel-type AlON:Mg,Mn, and BaAl 11 O 16 N:Eu [17][18][19].…”
Section: Introductionmentioning
confidence: 99%